MARX’S THEORY OF CRISIS IN THE CONTEXT OF FINANCIALIZATION. ANALYTICAL INSIGHTS ON THE CURRENT CRISIS - STRAVELAKIS, Nikos (Journal of Advanced Studies in Finance; Vol 3 No 2 (2012): JASF Volume III Issue 2(6) Winter 2012, 2012)
Lain by the fact that the present crisis was not preceded by a sharp decline in the rate of profit, Marxist and heterodox economists, investigate its’ causes in structural and institutional factors emerging in a «new phase» of capitalism dominated by «financialization» of capital. In this paper we argue that, in Marx, a sharp decline in the rate of profit is not a prerequisite for a crisis to emerge, if the rate of profit is already low. We argue further, that «financialization» of capital resulted, following the «great stagflation» of the 70s, from a strategy to battle low profitability by suppressing interest rates in order to increase the «rate of profit of enterprise». We show that this policy is, in the end, limited by the «rate of profit» and when the limit is reached the system collapses as it did in 2007. These analytical conclusions suggest that bank recapitalization will have restricted impact on output and employment because debts are already too high and profits too low for these funds to end up supporting corporate investment. Alternative policies should be applied otherwise a long period of capital impairment and high unemployment lies ahead of us.